Exploring happiness in different branches of psychology (The Journal of Psychology and Sociology, 2017)
This paper analyze the happiness phenomenon in different areas of psychology. The author describes the peculiarities of happiness understanding, its sources and determinants of experiencing happiness. Happiness as a pleasure, determines the specificity of regulation of libido energy entity disclosed in the psychoanalytic direction. Happiness as a self-development, provided by a desire for excellence and a sense of community in the individual psychology. Happiness as the peak of experiences associated with spirituality and responsibility in humanistic psychology. Happiness as a general life satisfaction, as the social well-being in behavioral and cognitive psychology.These studies of happiness represent an important role in the aspects of their appliance. The dependence of happiness on personal traits such as extroversion, sense of control, self-esteem and optimism, the ability to cooperate, openness to new experience, a positive sense of humor, the ability to build a comfortable relationship with the other, and plan for the future consciously. There was revealed the impact of wealth and money to happiness, which allowed to establish their significance mainly in countries with a low level of material security. The gender aspect emphasize the preference to money over men rather women. Women are more concerned with interpersonal relationships. Happiness is closely connected with the work, activity that contributes into self-realization and enjoying the process. Activities related to the short time period, stimulates the feeling of unhappiness. There is also an evidence that the highest value of happiness (the results of a longitudinal study) is warm relationships (family, friends, and society), the quality and stability of them, which are sources of better physical and mental health, longevity and, in the end, the subjective well-being. Analyzing the differences, the author reveals the sources and factors that stimulate feelings of happiness and poses the problem of a more integrated approach to the understanding of happiness. In connection with this, a differentiated approach to the study of the phenomenon of happiness as a substantial component of human life requires study both the structure and the relationship with the instrumental parameters providing a measure of wellbeing experience.Key words: happiness, pleasure, self-development, excellence, community, spirituality, responsibility, satisfaction, social well-being, the peak-experience.